Efeitos agudos e crônicos do exercício isométrico de preensão manual nas variáveis hemodinâmicas, neuromusculares e bioquímicas em idosos institucionalizados - Souza, Luiz Humberto Rodrigues (2019)
The objective of this study was to verify the acute and chronic effect of isometric handgrip (IHG) exercise on the hemodynamic and biochemical variables in the prehypertensive and hypertensive elderly subjects. Two studies were performed: 1º Ten hypertensive elderly (♀ = 7), 73.2 ± 2.2 years, 13.2 ± 3.1 years of hypertension, systolic blood pressure (SBP) 135.1 ± 6.5 mm Hg and diastolic blood pressure (DBP) of 76.6 ± 3.4 mm Hg were submitted to two acute sessions, a 3% control and another to 30% of maximal isometric voluntary contraction (MIVC) using a handgrip hydraulic dynamometer (Jamar, IL, USA). Participants completed eight sets of one minute isometric contraction, bilaterally, with one-minute pause. Blood pressure (BP) and heart rate (HR) were measured at rest and at 1, 5, 10, 15, 30, 45 and 60 min postexercise. Blood lactate and salivary nitric oxide (NO-) were collected at rest, 0, 30 and 60 min after exercise. 2º Thirty-three elderly (♀ = 15), 75.6 ± 1.2 years, were divided into three groups: hypertensive control (CG, n = 11), prehypertensive (PHG, n = 10) and hypertensive (HG = 12). Isometric handgrip training (IHT) was performed for 8 weeks, 3 times a week on non-consecutive days. The intensity and volume of the IHT were the same as in study 1. There was a non-exercise period after the 4- week IHT. Anthropometric and biochemical variables were evaluated before and after IHT. Hemodynamic and neuromuscular variables were measured before, during and after IHT. In study 1 there was a reduction of SBP after the session of 30% MVIC from the 10th min post-exercise (p < 0.05). At 60 minutes post-exercise, SBP was lower in the 30% vs. 3% MVIC (p = 0.006). There was no difference for the other variables (p > 0.05). In study 2, IHT reduced SBP and HR in both trained groups (PHG and HG). DBP and mean BP decreased only in HG (p < 0.05). Reductions in pressure levels induced by IHT were maintained during the period without IHG exercise. There was an inverse association of ΔTrolox/TBARS and Δlactate in relation to ΔSBP (p < 0.05). ΔTBARS was positively associated with reductions in DBP and HR after IHT (p < 0.05). IHT induced increase in NO- concentrations (p < 0.05). The Δ increase in absolute handgrip strength was associated with the reduction of ΔSBP, ΔDBP, ΔHR and with increase in ΔTrolox/TBARS and ΔNO- after IHT (p < 0.05). In conclusion, study 1 demonstrated that IHG exercise induced postisometric exercise hypotension in hypertensive elderly, with no association with lactate and NO- concentrations. In study 2, IHT also induced a reduction in BP and HR levels in prehypertensive and hypertensive elderly subjects. Endotheliumdependent flow mediated vasodilation and improvement in the redox state may be the possible mechanisms involved.